Spontaneous fracture of indwelling ureteral stents in patients treated with extracorporeal shock wave lithotripsy: Two case reports - (:unkn) unknown (Kluwer Academic Publishers, 1996)
Placement of indwelling ureteral stents adjunctive to ESWL treatment has been a widespread practice. We herein present two cases of spontaneous breakage of double pigtail ureteral stents and their management. Prevention of this complication may be possible by careful examination of the stents prior to insertion, by following the instructions of manufacturers on maximum time limits and by using stent logs to keep track of patients.